New Technologies in Humanitarian Logistics - Płaczek, Ewa; Świtalska, Angelika (Journal of Public Governance, 2023)
Objective: The aim of the article is to present new technologies and the possibilities of their implementation by entities involved in the implementation of logistics activities (humanitarian logistics). Research Design & Methods: To achieve the assumed goal, the method of analysing literature in the area of humanitarian logistics and new technologies related to the so-called digital revolution is used. Based on a literature review, general considerations on humanitarian logistics were related to the needs of business models of entities carrying out humanitarian aid activities in the implementation of new technologies. Findings: The article outlines the role and importance of new technologies in humanitarian logistics, which is an interesting and prospective research area. All presented examples of new technologies that are used in humanitarian logistics are extremely important for the easy, fast, and effective flow of information, finances, and supplies with humanitarian aid. The key to success is appropriate use of technology while ensuring the security of humanitarian supply chains.Implications / Recommendations: There is a need to deepen research in the field of humanitarian logistics, because identifying needs and barriers in the implementation of humanitarian logistics processes can significantly streamline and improve the effectiveness of humanitarian supply chains. Contribution / Value Added: The article shows that the role of new technologies treated as support for aid activities in humanitarian actions is the ability to quickly obtain and disseminate information that guarantees the effectiveness and efficiency of the undertaken actions. New technologies are an element of new business models of organisations involved in humanitarian aid. Article classification: theoretical/review paper